"Oh, Look, A Butterfly!" A Framework For Distracting Attackers To Improve Cyber Defense. (September 2018) - Gutzwiller, Robert; Ferguson-Walter, Kimberly; Fugate, Sunny; Rogers, Andrew
Inverting human factors can aid in cyber defense by flipping well-known guidelines and using them to de-grade and disrupt the performance of a cyber attacker. There has been significant research on how we perform cyber defense tasks and how we should present information to operators, cyber defenders, and analysts to make them more efficient and more effective. We can actually create these situations just as easily as we can mitigate them. Oppositional human factors are a new way to apply well-known research on human attention allocation to disrupt potential cyber attackers and provide much-needed asymmetric benefits to the defender.